Konsep Keamanan Untuk Anak Bermain di Kali Kendedes, Kecamatan Singosari, Kabupaten Malang - Finahari, Nurida; Soebiyakto, Gatot (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
Kali Kendedes in Singosari District, Malang Regency is a stream of water originating from a local source. This river is used as a children's playground. The observation results show that there is a potential for danger during activities, especially when children are swimming or playing in water. The writing of this article is aims to develop a safety concept for children playing in the Kendedes river. The technical application designed is a ladder up and down like a ladder in a swimming pool and hangers for visitors' things.